IMPLEMENTASI KEBIJAKAN REHABILITASI DAN REKLAMASI HUTAN DI KABUPATEN MAMUJU - Abd. Khalik (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to obtain an overview of how the implementation of forest rehabilitation and reclamation policies in Mamuju district. Data collection is done by interview and observation techniques. Data analysis was performed by qualitative methods, where the data obtained will be processed and analyzed by describing the implementation of forest rehabilitation and reclamation policies in Mamuju Regency. The results of the study indicate that the management of policies for implementing forest rehabilitation and reclamation can obtain optimal benefits from forest areas for the welfare of the community. So in principle all forest areas can be managed without ignoring characteristics. In harmony with its core functions, namely the functions of conservation, covert, and production.